Improving a coffee roastery using systematic layout planning - Case study of a coffee chain store - Niyomkha, Piraya; Ngarmpornprasert, Somying (Journal of Management Science Nakhon Pathom Rajabhat University, 2025)
This research aims to improve the spatial efficiency of a coffee roasting facility, with a particular focus on optimizing the storage area for green coffee beans prior to roasting. The goal is to expand the green bean storage room to prevent disruptions in the coffee roasting process. To achieve this, the researcher applied the Systematic Layout Planning (SLP) methodology in combination with the regulations of the Food and Drug Administration (FDA) to redesign the facility layout. This approach ensures both efficient use of space and continued safety for consumers. Operational data from the current facility were collected to develop three alternative layout designs. These new layouts were then compared with the existing one. The results indicated that Layout Design 3 provided the highest efficiency in warehouse space utilization. Specifically, the new layout increased the green bean storage area by 159.56%, expanded the roasted coffee storage area by 122.22%, reduced the transportation distance for green beans within the warehouse by 77.6%, and eliminated the need for electric forklifts in the handling process. Article history: Received 21 April 2025 Revised 12 September 2025 Accepted 15 September 2025 SIMILARITY INDEX = 4.59 %